Influence of asymmetries in the magnetic draping pattern at Titan on the emission of energetic neutral atoms. (March 2018) - Kabanovic, Slawa; Feyerabend, Moritz; Simon, Sven; Meeks, Zachary; Wulms, Veit
Abstract: We model the emission of energetic neutral atoms (ENAs) that are generated by the interaction between energetic ions from Saturn's magnetosphere and neutrals from the upper atmosphere of the giant planet's largest moon Titan. The trajectories of the parent ions and the resulting ENA emission morphology are highly sensitive to the electromagnetic field configuration near the moon. We therefore compare the ENA emission pattern for spatially homogeneous fields to the emission obtained from a magnetohydrodynamic (MHD) and a hybrid (kinetic ions, fluid electrons) model of Titan's magnetospheric interaction, by computing the trajectories of several billion energetic test particles. While the MHD model takes into account the draping of the magnetic field lines around Titan, the hybrid approach also considers the significant asymmetries in the electromagnetic fields due to the large gyroradii of pick-up ions from Titan's ionosphere. In all three models, the upstream parameters correspond to the conditions during Cassini's TA flyby of Titan. The shape, magnitude, and location of the ENA emission maxima vary considerably between these three field configurations. The magnetic pile-up region at Titan's ramside deflects a large number of the energetic parent ions, thereby reducing the ENA flux. However, the draped magnetic field lines in Titan's lobes rotate the gyration planes of the incident energetic ions, thereby facilitating the observable ENA production. Overall, the ENA flux calculated for the MHD model is weaker than the emission obtained for the electromagnetic fields from the hybrid code. In addition, we systematically investigate the dependency of the ENA emission morphology on the energy of the parent ions and on the upstream magnetic field strength. Highlights: Comparison of a MHD model with a hybrid model. Energy dependence of the ENA morphology. Imprint of asymmetries in the magnetic draping pattern on the ENA morphology.